GIS Analysis of Eighteen-year Trend in Land Use, Runoff, and Nonpoint Load Characteristics in the Lake Biwa–Yodo River Basin - NAKAMURA, Masahisa; SATO, Keisuke; TSUNO, Hiroshi; FUKUJU, Shinya; WADA, Keiko (Journal of Japan Society on Water Environment, 2020)
Making use of relevant Geographic Information System (GIS) data, an attempt was made to analyze the changes in the magnitude and spatial distribution of the land-based sources of nonpoint pollution loads for the entire Lake Biwa–Yodo River Basin over the 18-year period between 1991 and 2009. Specifically, the magnitudes per unit area of the runoff coefficient and of the COD, T-N and T-P pollutant loads, respectively, were computed and displayed as GIS visual images. The resulting GIS outputs indicate that the runoff coefficient increased along the riparian zones of rivers and around the lakeshore in the middle and lower basin regions, except for the mountainous regions. This implies that the pollutants flow directly into the immediately adjacent receiving waterbodies. Also, the trends of water pollutants were found to be affected by the unit load. The runoff coefficient and the COD loads were related with the progress of urbanization, indicating that the increase and decrease in T-N and T-P pollutant loads were caused by the conversion of land mainly from paddy agriculture to other agricultural purposes. In conclusion, it was confirmed that the results displayed in the form of GIS outputs are useful not only for numerical assessment but also for the assessment of spatial distributions.